Application of permeation liquid membrane and scanned stripping chronopotentiometry to metal speciation analysis of colloidal complexes - Domingos, R. F. (2013)
The potential of permeation liquid membrane (PLM) to obtain dynamic metal speciation information for colloidal complexes is evaluated by measurements of lead(II) and copper(II) complexation by carboxyl modified latex nanospheres of different radii (15, 35, 40 and 65 nm). The results are compared with those obtained by a well characterized technique: stripping chronopotentiometry at scanned deposition potential (SSCP). Under the PLM conditions employed, and for large particles or macromolecular ligands, membrane diffusion is the rate-limiting step. That is, the flux is proportional to the free metal ion concentration with only a small contribution from labile complexes. In the absence of ligand aggregation in the PLM channels, good agreement was obtained between the stability constants determined by PLM and SSCP for both metals.